PERANCANGAN TACTILE BOOK PENGENALAN HEWAN PELIHARAAN MENGGUNAKAN HURUF BRAILLE - MARLIANA APRIDA KHAIRUNNISA, Dra. Zubaidah, M.Sn., Eliya Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The development of learning media for the education of blindchildren are still very constrained by the small number of reading references. The common books found were books that only written  on braille letters. The use of Tactile book as media that can attract attention for blind childrens  because of the visual presentation with textures that touched on each objects.The pupose of designing tactile book media in this case is the introduction of pet as the main thing  explained for education. Blind children that who have limited vision will know and recognize pet  animals through this book. By using this tactile book, blind children can get to know its shapes, its  textutres by using the touching technique that explained.The method used in this design by using observation methodes, interviews and documentation. The method of analizing data was used the 5W+1H technique (what, where, who, when, why and how).The result achieved is this tactile book using Braille can attract the attention of the instructor or  parent to teach blind children so that they can get to know and learn and know the scope of learning education.Keywords : Tactile Book , Pet , Braille